Experimental determination of effective thermal conductivity of novel structures fabricated by selective laser melting - Ng, Lin Li (2018)
This report presents the development of a new facility to measure effective thermal conductivity of novel structures based on a steady-state technique. The reliability of the set-up was validated by conducting experimental measurements with a specimen of known thermal conductivity (e.g. Al6061). The results obtained show only a deviation of within 3%. The temperature gradient obtained from the experiments also showed that there was minimal heat losses from the set-up, therefore ensuring one-dimensional (1D) heat conduction across the test specimens. Subsequently, a set of porous structures was designed based on constructal theory, whereby its effective thermal conductivity was experimentally determined with the newly developed thermal conductivity test facility. Comparisons against two other sets of porous structures produced by Selective Laser Melting (SLM) technique were carried out. The SLM fabricated structures were shown to have different bulk thermal conductivity. However, with a well-established empirical correlation by Calmidi and Mahajan [1], the effective thermal conductivity of the structures based on the same bulk thermal conductivity were obtained. The comparison shows that the novel structures performed better than the honeycomb structures at porosities between 0.77 to 0.84, while surpassing the effective thermal conductivities of all Rhombi-Octet specimens with porosity of 0.85. Finally, it was also concluded that thermal stress relieve heat treatment results in significant increase in thermal conductivity of SLM fabricated solid and porous structures.